Heat capacity of compensated F/AF bilayers - Silva, M. L. (2005)
We report a theoretical study of the magnetic heat capacity, cV(T), of exchange coupled compensated ferromagnet/antiferromagnetic bilayers. We show that cV(T) may display a large peak at the temperature TR where the interface magnetic frustration induces a 90° reorientation of the F layer. We study Fe/FeF2 bilayers and show that TR and the magnitude of the cV(T) peak depend on the strength of the interface exchange. We suggest how the sign of the interface exchange energy parameter can be investigated using features produced by external fields.